Kindheit und Arbeit Wege zum besseren Verständnis arbeitender Kinder - Liebel, Manfred (Verlag Barbara Budrich, 2020)
The book shows that the work of children is neither a relic of times gone by nor a relic of societies lagging behind, and questions the reflexes and supposed certainties and judgments about it. On the basis of numerous studies from different continents, it sharpens the awareness of the diversity of forms and meanings that work for children can have, and explains why previous measures against child labour must be questioned.